Disparities in Health Care–Associated Infections in the NICU - Liu, Jessica; Sakarovitch, Charlotte; Sigurdson, Krista; Lee, Henry C.; Profit, Jochen (American Journal of Perinatology, 2020)
Objectives This study aimed to examine multilevel risk factors for health care–associated infection (HAI) among very low birth weight (VLBW) infants with a focus on race/ethnicity and its association with variation in infection across hospitals.Study Design This is a population-based cohort study of 20,692 VLBW infants born between 2011 and 2015 in the California Perinatal Quality Care Collaborative.Results Risk-adjusted infection rates varied widely across neonatal intensive care units (NICUs), ranging from 0 to 24.6% across 5 years. Although Hispanic infants had higher odds of HAI overall, race/ethnicity did not affect the variation in infection rates. Non-Hispanic black mothers were more likely to receive care in NICUs within the top tertile of infection risk. Yet, among NICUs in this tertile, infants across all races and ethnicities suffered similar high rates of infection.Conclusion Hispanic infants had higher odds of infection. We found significant variation in infection across NICUs, even after accounting for factors usually associated with infection.
Keywords: infant; health care–associated infection; disparity; risk factors